2006
DOI: 10.1523/jneurosci.1282-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Multi-Neuron Firing Patterns in Primate Retina

Abstract: Current understanding of many neural circuits is limited by our ability to explore the vast number of potential interactions between different cells. We present a new approach that dramatically reduces the complexity of this problem. Large-scale multi-electrode recordings were used to measure electrical activity in nearly complete, regularly spaced mosaics of several hundred ON and OFF parasol retinal ganglion cells in macaque monkey retina. Parasol cells exhibited substantial pairwise correlations, as has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
702
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 457 publications
(747 citation statements)
references
References 64 publications
39
702
2
4
Order By: Relevance
“…Previous studies have also used pairwise approximations in other contexts, but the underlying variables represented the dynamics of specific cellular components or other physical entities such as proteins or neurons (24)(25)(26)(27)(28)(29)(30). Most notably, a recent study in cancer cells demonstrated that the expression of some proteins in response to combinations of drugs can be predicted from their responses to smaller drug combinations (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also used pairwise approximations in other contexts, but the underlying variables represented the dynamics of specific cellular components or other physical entities such as proteins or neurons (24)(25)(26)(27)(28)(29)(30). Most notably, a recent study in cancer cells demonstrated that the expression of some proteins in response to combinations of drugs can be predicted from their responses to smaller drug combinations (24).…”
Section: Discussionmentioning
confidence: 99%
“…The analog signal from each electrode was sampled at 20 kHz. This system has been used previously to study the encoding of visual motion and multineuron firing patterns in mosaics of parasol cells in the primate retina (Frechette et al, 2005;Shlens et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The existence of a low-dimensional parameterization of the retinal activity (8)(9)(10)(11) is an interesting and encouraging result. Naively, one may be tempted to assign to the inferred parameters a simple interpretation: The fields could represent the external stimuli, and the couplings could reflect the physiological interactions between the cells.…”
mentioning
confidence: 98%